Implementation of Whistleblowing Management System in Law Enforcement Institutions for Corruption Crimes According to Clause 8 of ISO 37002:2021 - Meirianti Zulfa Catur Putri; Purwatiningsih Lisdiono (Green Publisher Indonesia, 2024)
Whistleblowing System has been internationally recognized as an effective way to combat corruption, both within an organization and at a national level. This case study research aims to improve the governance of complaint handling at Institution XYZ, particularly in the operations related to complaint management, through a gap analysis using Clause 8 of ISO 37002:2021. Therefore, this study is limited to assessing the conformity of complaint handling in accordance with Clause 8 of ISO 37002:2021. Data was obtained through document analysis and in-depth interviews. The research data was analyzed descriptively and qualitatively to gain a deep and comprehensive understanding of the phenomenon, focusing on the meaning and interpretation of the data. Based on the analysis, it was found that the implementation of the Whistleblowing Management System (WMS) had been partially carried out by Institution XYZ. Improvements are needed in the determination of locations for raising awareness about the complaint channels based on the number of complaints, as well as in developing policies for the protection of whistleblowers and employees. This study is expected to serve as an analytical tool for policy-making at Institution XYZ and to provide information on WMS implementation for other institutions.